PELAKSANAAN PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN PESISIR KECAMATAN LIMAPULUH KOTA PEKANBARU TAHUN 2017 - Veny Risvayanti; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
In order to improve the quality of housing and settlements, the government launched a city program without slums (KOTAKU) starting in 2016. The No Slum City Program (KOTAKU) is a program implemented nationally in 271 Regencies / Cities in 34 Provinces that become